1998
DOI: 10.1108/03068299810212676
|View full text |Cite
|
Sign up to set email alerts
|

Technology transfer models across cultures: Brunei‐Japan joint ventures

Abstract: This paper presents the main finding of the study based on the experience of Brunei-Japan joint ventures in cross-cultural technology transfer. Some of the other findings of the study have been presented at APEC-HRD-BMN seminars/workshop held at Taipei

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Therefore an organization's culture which is omnipresent needs to be understood. This effectiveness is also considered to relate to both the diffusion and management of technology transfer [7]. The types listed in Table 1 are considered useful in formulating the basis of the Analysis of an organization's culture.…”
Section: Cultural Barriersmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore an organization's culture which is omnipresent needs to be understood. This effectiveness is also considered to relate to both the diffusion and management of technology transfer [7]. The types listed in Table 1 are considered useful in formulating the basis of the Analysis of an organization's culture.…”
Section: Cultural Barriersmentioning
confidence: 99%
“…If there is a significant gap in the technological capability between the transferor and the transferee, the transferee might have difficulty in learning and understanding the essence of technology. [7] D. Market BARRIERS: There are consequently a variety of market barriers to effective technology transfer that prevent private companies from being easily incorporated into international policy and a host of informational, support, and capacity problems in supporting organizations when they do. Past experience in developing countries has indicated that market barriers may diminish international investment on technology transfer.…”
Section: Cultural Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Technology transfer is taking place in tandem with foreign direct investment in joint ventures. Japan is one of the most active countries in this regard (Hussain, 1998).…”
Section: Marketing In Brunei Indonesia and Malaysia Bruneimentioning
confidence: 99%